Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kepuasan Kerja Pegawai Badan Pengelolaan Keuangan Daerah (BPKD) Kabupaten Tambrauw - Andrei Sakharov Maryen; Lili Sarce Joi Sapari; James Roby Pariry (Universitas Nusantara PGRI Kediri, 2023)
BPKD Tambrauw Regency as an institution of public interest requires maximum efficiency in terms of increasing work results to achieve organizational goals. Work motivation and transformational leadership style are closely related to employee job satisfaction because they are driving factors that generate morale in humans to work together, efficiently and integratedly. The aim is to determine the effect of transformational leadership style and work motivation on employee job satisfaction. Sampling is based on a sample of the population, ie. H. All population groups are included in a sample of 30 respondents. This type of research is quantitative with multiple linear regression analysis by conducting the t test, F test and test the coefficient of determination. The regression equation is determined from the results of calculations performed using multiple linear regression analysis Y=9.436+0.040X1+0.504X2. Based on the results and discussion, it can be concluded that work motivation has a significant effect on job satisfaction of Tambrauw Regency Regional Economic Implementing Agency (BPKD) employees, while transformational leadership style has no effect on job satisfaction. However, at the same time, work motivation has a significant influence on employee job satisfaction. Tambrauw Regency Regional Economic Administration Agency (BPKD).